Design of Internet of Thing (IoT)-based Control and Monitoring System of Eco-Aquaculture - Jonathan Hervianto; Raden Sjarief Widjaja; Sintia Megawati; Yuda Apri Hermawan; Totok Yulianto (International Journal of Marine Engineering Innovation and Research, 2025)
Aquaculture plays a vital role in global food supply, contributing nearly 43% of the food consumed by humans. The rapid growth in aquaculture production demands a significant amount of electricity, which accounts for approximately 40% of the total energy costs. The primary energy sources in aquaculture used fossil fuels, it can be reduced by utilizing alternative energy sources. This research aims to develop a prototype of a floating net cage using an Internet of Things (IoT)-based water quality monitoring system powered by solar energy. The water quality parameters monitored in this study include temperature, pH, salinity, and dissolved oxygen levels. The sensors used for monitoring these parameters have undergone testing. The results indicate that the sensors can perform accurate measurements with over 90% accuracy. The solar panels installed in the system are capable of generating sufficient power to meet the operational demands, allowing the system to operate for approximately two days without sunlight. By maintaining well-controlled aquatic environmental conditions through IoT-based monitoring and control systems supported by renewable photovoltaic solar energy, environmentally friendly aquaculture operations can be conducted efficiently and productively. Ultimately, this leads to the production of high-quality aquaculture products, cost-effective operations, and the utilisation of eco-friendly energy sources.